Quantum cryptography via a wavelength router for internet security - Threepak, T.; Mitatha, S.; Luangvilay, X.; Yupapin, P. P. (My University, 2010)
We propose a new system of quantum cryptography for internet security using Gaussian pulses propagating within a nonlinear ring resonator system, quantum processor, and a wavelength router. To increase the channel capacity and security, the multiplexer is operated incorporating a quantum processing unit via an optical multiplexer. The transmission part can be used to generate the high capacity quantum codes within the series of microring resonators and an add/drop filter. The receiver part can be communicated by using the quantum key (quantum bit, qubit) via a wavelength router and quantum processors. The reference states can be recognized by using the cloning unit, which is operated by the add/drop filter, where the communication between Alice and Bob can be performed. Results obtained have shown that the correlated photons can be generated and formed the entangled photon pair, which is allowed to form the secret key between Alice and Bob. In application, the embedded system within the computer processing unit is available for quantum computer. Furthermore, such a concept is also available for internet application via hybrid communications, for instance, wire/wireless, satellite, which can be used to form the internet security. © 2010 Wiley Periodicals, Inc.
Keywords: internet security; quantum computer; quantum cryptography; quantum signal processing